Organizational Inertia, Digital Capabilities, Digital Transformation, and Firm Competencies - Utomo, Adhi Ari; Maulida, Mira; Musa, Soebowo (The South East Asian Journal of Management, 2023)
Research Aims: This research aims to investigate the impact of organizational inertia on digital capabilities and digital transformation to optimize firm competencies. Design/Methodology/Approach: The dataset was produced through a quantitative survey of 125 firms in Indonesia using the Structural Equation Model (SEM) to analyse the data. Research Findings: The results of this study indicate that organizational inertia indirectly impacts firm competencies through digital capabilities and digital transformation. Organizational inertia impacts digital capabilities, not digital transformation, whereas digital capabilities impact digital transformation and a firm’s competencies. Theoretical Contribution/Originality: This study contributes to the literatures on organizational behaviour and strategic management by investigating the impact of organizational inertia on the success of digital transformation and its impact on firm competencies. Managerial Implication in the South East Asian context: The research findings embrace digital transformation practices by enhancing firms' digital capabilities, particularly in digital transformation response, digital opportunity identification, innovative digital technology product development, acquisition, and mastering state-of-the-art digital technologies. Research Limitation & Implications: The findings of this study reflect the conditions of numerous enterprises operating in several industry sectors in Indonesia during the chaotic post-COVID-19 pandemic period. Furthermore, the survey respondents constitute various firms with various digital transformation implementation levels.